A comparison of California's ALRA and the Federal NLRA - P Martin (California Agriculture, 1983)
California's 1975 Agricultural Labor Relations Act (ALRA) granted all farmworkers the right to form or join unions and to bargain collectively with farm employers, or to refrain from union activity, and to make these decisions without interference from employers. The law specified the rights of farmworkers, defined the unfair labor practices that employers and unions can commit, and established an Agricultural Labor Relations Board (ALRB) to supervise representation elections and to rule on unfair-labor-practice charges.